Faktor yang Mempengaruhi Pendapatan Keluarga Miskin di Kecamatan Maesan Kabupaten Bondowoso - Moehammad Fathorrazi; Dewa Murti; Fivien Muslihatinningsih (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
This study aims to determine the factors that affect the income of the poorest families in the district Maesan the regency by using the method of analysis Regression (Regression Model Multiplier). Data used in this study are primary data derived from interviews, questionnaire method, the method of observation (cross section) with a research area in District Maesan regency. The regression results obtained from this study indicate that education (X1) and age (X2) has positive effect on revenues. The number of dependents (X3) and the type of work (X4) negative effect on revenue. The probability value of each independent variable is education (X1) of 0.0000, age (X2) of 0.0000, the number of dependents (X3) at 0.0000 and the type of work (X4) of 0.7765. This shows that in the study of factors that affect the income of poor families in the District Maesan Bondowoso,variables that influence the educational variables, variables of age, and a variable number of dependents who have significant influence on the income variable. Variable type of work does not significantly influence the income variable. Keywords: income, education, age, total family dependents and The job type